Karakteristik Beton Mutu FC 30 Dengan Menggunakan Limbah Peleburan Baja (Slag) Dan Pembakaran Batubara (Fly Ash) - Nur Rohman, Muhammad; Simanihuruk, Bertinus; Dewita, Hikma (Fakultas Teknik dan Teknologi - TANRI ABENG UNIVERSITY, 2025)
The use of slag and fly ash waste for building materials is not optimal, because it contains heavy metal oxides. With the issuance of Government Regulation no. 22 of 2021, dust resulting from burning coal from Steam Power Plants and other activities is not included as B3 waste. With research on the use of fly ash and slag to increase the compressive strength of concrete, research was carried out in the laboratory to determine the optimal composition for the use of slag and fly ash as a substitute for coarse aggregate and cement in concrete mixtures. By testing in the laboratory, results were obtained with variations in slag. 10, 20% and 30% with fly ash remaining at 10% as a concrete mixture by comparing with a normal concrete mixture. From the test results, the results obtained were that the addition of slag and fly ash waste could reduce the heat of concrete at FC 30, producing concrete compressive strength close to normal concrete compressive strength, namely 26.31 MPa for 7 days, 33.11 MPa at 28 days, and 39.61 MPa at 56 days with composition10% slag and 10% fly ash with the slump value achieved was 6 cm which makes it difficult to make concrete. The addition of 20% and 30% slag with 10% fly ash produces a compressive strength of concrete that is lower than the concrete compressive strength of FC 30. The appropriate composition to use is 10% slag as a substitute for coarse aggregate and 10% fly ash as a cement substitute